Synthesis some imines and azo compounds derived from 4-(2-amino-3,4-dimethoxyphenyl)-3-methylfuroxan - Đĩnh và cộng sự, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
Some imines and azo compounds containing furoxan and benzene rings has been prepared starting from 4-(2-amino-3,4-dimethoxyphenyl)-3-methylfuroxan. The structure of reported compounds has been confirmed by UV, IR, a NMR spectroscopy.